Frequency of pathogenic and enteroadherent Escherichia coli in patients with inflammatory bowel disease and controls. Issue 7 (July 1997) - Schultsz, C; Moussa, M; van Ketel, R; Tytgat, G N; Dankert, J
Abstract : AIMS: To determine whether inflammatory bowel disease (IBD) is associated with pathogenic or enteroadherent Escherichia coli. METHODS: A least two stool specimens and one rectal biopsy were taken from 30 patients with IBD and from 20 controls. A large number of E coli-like colonies cultured from each stool sample and biopsy was tested, using DNA probes, for the presence of genes encoding shiga-like toxins, invasiveness, attachment-effacement and the ability to adhere to HEp-2 cells. Similarity among isolates from stool samples and rectal biopsies was determined by random amplified polymorphic DNA (RAPD) analysis. RESULTS: Enterohaemorrhagic and enteroinvasive E coli were not found in samples from either patients or controls. No significant difference in the detection rate of enteroadherent E coli between patients and controls was found. Rectal biopsies from 11 of 28 patients with IBD and 4 of 18 controls contained E coli, which hybridised with probes for detection of genes encoding diffuse adherence to HEp-2 cells, or encoding P-pili (p = 0.2). Enteroadherent E coli isolated from two or three stool specimens from the same patient or control appeared to be identical by RAPD analysis, and are considered to be residents in the colon. Probe positive isolates obtained from stool specimens and corresponding rectal biopsies were always identical on RAPD analysis. CONCLUSIONS: E coli strains possessing adherence factors reside in the large intestine and adhere to the rectal mucosa, irrespective of the presence of colitis.